2020
DOI: 10.4158/ep-2019-0470
|View full text |Cite
|
Sign up to set email alerts
|

The Guided Transfer of Care Improves Adult Clinic Show Rate

Abstract: Objective: Every year, 500,000 youths in the U.S. with chronic disease turn 18 years of age and eventually require transfer to adult subspecialty care. Evidence-based interventions on the organization of transfer of care are limited, although engagement and retention in adult clinic are considered appropriate outcomes. Sustained continuity of care improves patient satisfaction and reduces hospitalization. Methods: We conducted a prospective, nonrandomized cohort study of patients with pediatric endocrine cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
1
4
0
1
Order By: Relevance
“…More concerningly still, a significant proportion of these patients had polyarthritis, which is known to be associated with poorer long‐term outcomes than other JIA subtypes, with higher rates of severe limitation of function and disability in adulthood 8 . Our findings are consistent with studies in other tertiary centres in which suboptimal transfer of care was found to occur in 34–59% of patients with JIA and other chronic illnesses 5,9–12 . Taken together, these data highlight the importance of having mechanisms in place to ensure ongoing care has been established when transitioning JIA patients to adult care.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…More concerningly still, a significant proportion of these patients had polyarthritis, which is known to be associated with poorer long‐term outcomes than other JIA subtypes, with higher rates of severe limitation of function and disability in adulthood 8 . Our findings are consistent with studies in other tertiary centres in which suboptimal transfer of care was found to occur in 34–59% of patients with JIA and other chronic illnesses 5,9–12 . Taken together, these data highlight the importance of having mechanisms in place to ensure ongoing care has been established when transitioning JIA patients to adult care.…”
Section: Discussionsupporting
confidence: 85%
“…We found that the use of ‘backstop’ appointments – appointments at our centre scheduled intentionally after the estimated date of initial adult review – more than doubled the rate of documented transfer of care. To our knowledge, this is the first study to demonstrate this and provides evidence to support their use, particularly for services that do not have the capacity to implement guided transfer of care models in which paediatric specialists participate as patients are introduced to adult providers and corresponding models of care 11 …”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Bessere Zusammenarbeit/Kommunikation mit Erwachsenenmedizinern [24,25]. Auch die Daten von Studien aus den USA, Australien, Israel, Spanien und Italien weisen darauf hin, dass eine systematische Transition zu einer Verbesserung der HbA 1c -Werte führen kann [7,[26][27][28][29].…”
Section: Verbesserungsmöglichkeiten Anzahl (N)unclassified
“…The entire dynamic process in which the paediatric patient is guided towards AC is called ‘transition’, whereas ‘transfer’ is the moment when the patient leaves PC and AC takes over. The transfer of adolescents from PC to AC is a crucial but vulnerable step in the care of adolescents with a chronic disorder ( 4 , 5 ). Previous studies have shown that up to 25% of young adults with endocrine disorders are lost to follow-up after moving out of paediatric care ( 6 , 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%